Pengaruh Persepsi Mahasiswa Tentang Koperasi Terhadap Minat Berkoperasi Mahasiswa Pendidikan Ekonomi - Artin, Endah Aisah Eka Yuni; Kamalia, Putri Ulfa (Jurnal Riset Pendidikan Ekonomi, 2024)
This research aims to determine the influence of student perceptions about cooperatives on economic education students' interest in cooperatives. This research is a causal quantitative research, with 79 students as respondents. Data collection technique by distributing Google form links online. The research instrument used in this research was a questionnaire. The data analysis method used is simple linear regression. The results of this research show that students' perceptions of cooperatives have a positive influence on students' interest in cooperatives. Things that can be done to increase economic education students' interest in cooperatives include providing project-based assignments, student internship programs in cooperatives, creating a family atmosphere in cooperatives, creating innovation in the products offered and the need to improve cooperative management. So with these steps, economic education students' interest in cooperatives will increase.